PENGARUH PENAMBAHAN BENTONIT TERMODIFIKASI SEBAGAI PENGISI TERHADAP SIFAT MEKANIK DAN PENYERAPAN AIR KOMPOSIT EPOKSI - Alvian; Kenrick; Iriany (Talenta Publisher (Universitas Sumatera Utara), 2016)
Research about the application of modified bentonite as filler in epoxy has been done for the purpose of getting the best composition of modified bentonite as filler at epoxy composite to obtain the best mechanical properties such as tensile strength, impact strength and the water absorption. In this research, epoxy resin mixed with bentonite which have been modified using cetyltrimethylammonium bromide (CTAB) surfactant with various concentrations of 0,05M, 0,1M, and 0,15M. Modified bentonite filler and TiO2 then mixed with epoxy resin with various concentration of 5%, 10%, 15%, and 20% of filler from the total mass of the composite and then the composite was produced with hand lay-up method. The result of FTIR characterization showed that the bond between matrix and the filler produced was only interfacial bonding. The result of the mechanical properties test indicated that 5% of filler composition with 0,1M of surfactant concentration obtained the maximum value of tensile strength and mechanical strength respectively 33,667 MPa and 12564,9 J/m2. The result of mechanical properties test was supported by analysis of Scaning Electron Microscopy (SEM). On the test of water absorption, the water absorption capacity increased along with the increased of filler composition.